2022
DOI: 10.1177/23982128221079556
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for trait- and state-level urgency moderating the daily association between negative affect and subsequent alcohol use in two college samples

Abstract: It remains unclear whether the negative reinforcement pathway to problematic drinking exists, and if so, for whom. One idea that has received some support recently is that people who tend to act impulsively in response to negative emotions (i.e. people high in negative urgency) may specifically respond to negative affect with increased alcohol consumption. We tested this idea in a preregistered secondary data analysis of two ecological momentary assessment studies using college samples. Participants ( N = 226)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Participants reported consuming marijuana on 20.4% of study days. Consistent with prior EMA work (Dora, Piccirillo, et al, 2022;Dora, Schultz, et al, 2022;Trampe et al, 2015;Zelenski & Larsen, 2000), participants reported relatively low levels of momentary negative affect (M = 17.62, SD = 14.92) and moderate levels of momentary positive affect (M = 50.00, SD = 22.27) on average.…”
Section: Descriptive Statisticssupporting
confidence: 74%
See 3 more Smart Citations
“…Participants reported consuming marijuana on 20.4% of study days. Consistent with prior EMA work (Dora, Piccirillo, et al, 2022;Dora, Schultz, et al, 2022;Trampe et al, 2015;Zelenski & Larsen, 2000), participants reported relatively low levels of momentary negative affect (M = 17.62, SD = 14.92) and moderate levels of momentary positive affect (M = 50.00, SD = 22.27) on average.…”
Section: Descriptive Statisticssupporting
confidence: 74%
“…A recent large-scale meta-analysis (Dora, Piccirillo, et al, 2022; Dora, Schultz, et al, 2022) of this literature, which included a large number of college student samples, found that people were more likely to drink on days that they reported higher positive affect (the daily association between negative affect and alcohol use, on the other hand, was estimated to be close to zero). As such, we are inclined to interpret this result as another piece of evidence that, specifically in college student samples (Dora, Piccirillo, et al, 2022; Dora, Schultz, et al, 2022; Wycoff et al, 2018), people's substance use (alcohol and marijuana) tends to be preceded by positive (rather than negative) emotional experiences. Our specification curve analysis shows further that the discrete emotions one assesses might matter also when it comes to positive affect (we found no effects for friendly and engaged ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, given that recent research indicates that drinking in everyday life often seems to follow high positive affect (Dora, Kuczynski, et al, 2022; Dora, Schultz, et al, 2022), we repeated our analyses comparing the positive to the neutral mood induction. Unsurprisingly (given the small effect of the positive induction on mood), these models provided no evidence for an Induction × Sample interaction on drift rate and boundary separation associated with alcohol (BF 01 [drift rate] = 5.63, BF 01 [boundary separation] = 19.55) and food (BF 01 [drift rate] = 1.49, BF 10 [boundary separation] = 2.12), with Bayes factors ranging from strong evidence against our hypothesis to inconclusive.…”
Section: Resultsmentioning
confidence: 99%